Relationship between solids flux and froth features in batch flotation of sulphide ore - Yang, X.; Aldrich, Chris (Elsevier, 2005)
The froth features in the batch flotation of a sulphide ore were investigated by using the digital image parameters of the froth, the small number emphasis (N sne ), the average grey level (D agl) and the instability number (N ins), under different conditions of impeller speeds and aeration rates. It is found that the value of N sne is strongly dependent on the average bubble size of the froth and D agl on the volume fraction of solid in the froth, and the froth features during the batch flotation are influenced by impeller speed and aeration rate. A Kinetic model of the concentrate solid flux was developed which relates the flotation process to the image parameters, N sne and D agl of the froth and predictions are well consistent with the experimental data.